2018
DOI: 10.1002/glia.23445
|View full text |Cite
|
Sign up to set email alerts
|

The roles of extracellular vesicle microRNAs in the central nervous system

Abstract: MicroRNAs (miRNAs) are small, highly conserved non-coding RNA molecules that post-transcriptionally regulate protein expression and most biological processes. Mature miRNAs are recruited to the RNA-induced silencing complex (RISC) and target mRNAs via complementary base-pairing, thus resulting in translational inhibition and/or transcript degradation. Here, we present evidence implicating miRNAs within extracellular vesicles (EVs), including microvesicles and exosomes, as mediators of central nervous system (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 125 publications
0
30
0
Order By: Relevance
“…In contrast to GJs and TNTs, the encapsulation of miRNA into exosomes allows intercellular transport across long distances without direct cell‐cell contacts. A plenty of studies have proven the exosome mediated functional shuttling of miRNA in multiple cell types . For example, the uptake of miR‐222‐3p enriched exosomes by macrophages, released from ovarian cancer cells, led to stimulation of the STAT3 pathway which in turn promotes macrophage activation .…”
Section: Alternative Routes For Intercellular Mirna Exchangementioning
confidence: 99%
“…In contrast to GJs and TNTs, the encapsulation of miRNA into exosomes allows intercellular transport across long distances without direct cell‐cell contacts. A plenty of studies have proven the exosome mediated functional shuttling of miRNA in multiple cell types . For example, the uptake of miR‐222‐3p enriched exosomes by macrophages, released from ovarian cancer cells, led to stimulation of the STAT3 pathway which in turn promotes macrophage activation .…”
Section: Alternative Routes For Intercellular Mirna Exchangementioning
confidence: 99%
“…Many reports have shown that miRNAs are released from the cells in the extracellular environment through exosomes. Recent studies have shown that exosomal cargo of cellular proteins, lipids, and miRNAs act as mediators of intercellular crosstalk between the effector and recipient cells [9]. Their ability to protect cargo contents from degradation and traverse across the intact BBB to reach the circulation highlights their importance as potential disease biomarkers [10].…”
Section: Introductionmentioning
confidence: 99%
“…44,45 A key characteristic of EVs is their ability to penetrate the blood-brain barrier and release related RNAs and proteins into the central nervous system. 46 Studies have shown that MSCs-EVs can exert neuroprotective effects by promoting the growth and repair of blood vessels, repairing and regenerating nerve cells, and inhibiting apoptosis of nerve cells after stroke. 47 Studies have shown that EVs can stimulate the growth of nerve cells, 48 induce neuronal proliferation, 49 increase the number of axons, 50 regulate the peripheral immune response, 51 reduce the area of infarction after cerebral ischemia, improve brain function, 12 and promote axonal growth and white matter recovery.…”
Section: Discussionmentioning
confidence: 99%